Genetic Deletion of GABAA Receptors Reveals Distinct Requirements of Neurotransmitter Receptors for GABAergic and Glutamatergic Synapse Development - Duan, Jingjing; Pandey, Saurabh; Li, Tianming; Castellano, David; Gu, Xinglong; Li, Jun; Tian, Qingjun; Lu, Wei (Frontiers in Cellular Neuroscience, 2019)
In the adult brain GABAA receptors (GABAARs) mediate the majority of synaptic inhibition that provides inhibitory balance to excitatory drive and controls neuronal output. In the immature brain GABAAR signaling is critical for neuronal development. However, the cell-autonomous role of GABAARs in synapse development remains largely unknown. We have employed the CRISPR-CAS9 technology to genetically eliminate GABAARs in individual hippocampal neurons and examined GABAergic and glutamatergic synapses. We found that development of GABAergic synapses, but not glutamatergic synapses, critically depends on GABAARs. By combining different genetic approaches, we have also removed GABAARs and two ionotropic glutamate receptors, AMPA receptors (AMPARs) and NMDA receptors (NMDARs), in single neurons and discovered a striking dichotomy. Indeed, while development of glutamatergic synapses and spines do not require signaling mediated by these receptors, inhibitory synapse formation is crucially dependent on them. Our data reveal a critical cell-autonomous role of GABAARs in inhibitory synaptogenesis and demonstrate distinct molecular mechanisms for development of inhibitory and excitatory synapses.